Pressure-enhanced decomposition of Ag3[Co(CN)6]. (February 2015) - Catafesta, J.; Rovani, P.R.; Perottoni, C.A.; Pereira, A.S.
Abstract: The structural stability of silver hexacyanocobaltate, Ag3 [Co(CN)6 ], was investigated at high pressure and moderate temperature using X-ray diffraction, Raman spectroscopy, and Fourier Transform Infrared spectroscopy. Pressure induced amorphization (PIA) or pressure enhanced decomposition were observed depending of the processing conditions. In situ X-ray diffraction analysis unequivocally confirmed the PIA at room temperature for pressures higher than 13 GPa. The usual decomposition temperature at ambient pressure, 227 °C, decreased to 180 °C at 7.7 GPa, and to 150 °C at 14 GPa. The decomposition products after moderate heating at high pressure are at least two phases: crystalline elemental silver and an amorphous phase containing the remaining elements (Co, C and N), which presents a Raman spectrum similar to that observed for amorphous graphite-like carbon nitride (CNx ). Our findings confirm the previously reported pressure induced amorphization of Ag3 [Co(CN)6 ] at room temperature, and indicate that this amorphization is the result of a kinetically hampered decomposition.